Answer:
(3, 3 )
Step-by-step explanation:
Given the 2 equations
3x - y = 6 → (1)
6x + y = 21 → (2)
Adding the 2 equations term by term will eliminate y, that is
(6x + 3x) + (y - y) = (21 + 6), that is
9x = 27 (divide both sides by 9 )
x = 3
Substitute x = 3 into either (1) or (2) and solve for y
Using (2), then
(6 × 3) + y = 21
18 + y = 21 ( subtract 18 from both sides )
y = 3
Solution is (3, 3 )
First, add the ratio together to get the denominator of the fraction you will use to determine the share. 3+5= 8. Now, you have two fractions: 3/8 and 5/8. Next, just find 3/8 and 5/8 of 56 to get your answers:
(56÷8)×3= <span>£21
</span>and
(56÷8)×5= <span>£35</span>
Answer:
ones
Step-by-step explanation:
63
6=60
3=3
so it is in the ones place
16. M = 1/5
17. M =3
18. Slope 1/4 and y-intercept (0,2)